Implications for UK coal-fired power stations of a move to a particulate matter standard based on PM2.5. (8th February 2011) - Griffiths, Stephen; Booth, Victoria; Lennard, Robert
The contribution of UK coal-fired power stations to ambient PM2.5 concentrations has been assessed using short- and long-range modelling. The results suggested a minimal contribution from power stations to both local and regional concentrations of PM2.5 relative to the standards in the proposed European Directive on Ambient Air Quality and only a modest contribution in terms of overall UK PM2.5 levels. Secondary particulate showed a different concentration pattern to primary particulate, the latter being focused on urban areas with high populations. This has important implications for exposure if, as toxicological studies suggest, the toxic component lies predominantly within primary fraction.